2014
DOI: 10.1111/pce.12328
|View full text |Cite
|
Sign up to set email alerts
|

Global reprogramming of transcription and metabolism in Medicago truncatula during progressive drought and after rewatering

Abstract: Medicago truncatula is a model legume forage crop native to the arid and semi-arid environments of the Mediterranean. Given its drought-adapted nature, it is an ideal candidate to study the molecular and biochemical mechanisms conferring drought resistance in plants. Medicago plants were subjected to a progressive drought stress over 14 d of water withholding followed by rewatering under controlled environmental conditions. Based on physiological measurements of plant water status and changes in morphology, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 97 publications
8
150
0
2
Order By: Relevance
“…This involves treatments such as cutting and air drying leaves and/or roots or induction of osmotic shock through the application of highly concentrated osmotica such as polyethylene glycol or mannitol (Kreps et al, 2002;Seki et al, 2002;Kawaguchi et al, 2004;Kilian et al, 2007;Weston et al, 2008;Fujita et al, 2009;Abdeen et al, 2010;Deyholos, 2010;Mizoguchi et al, 2010). These experiments have substantially increased our knowledge of molecular responses under severe drought stress, but they do not always reflect physiological conditions experienced by drought-stressed soil-grown plants (Bechtold et al, 2010(Bechtold et al, , 2013Harb et al, 2010;Wilkins et al, 2010;Lawlor, 2013;Zhang et al, 2014). Physiological responses such as stomatal conductance, photosynthetic performance, and metabolic changes are usually not measured during the progression of the drought stress, and the varied nature of the stress induction treatments makes comparative analysis between experiments problematic.…”
Section: Introductionmentioning
confidence: 99%
“…This involves treatments such as cutting and air drying leaves and/or roots or induction of osmotic shock through the application of highly concentrated osmotica such as polyethylene glycol or mannitol (Kreps et al, 2002;Seki et al, 2002;Kawaguchi et al, 2004;Kilian et al, 2007;Weston et al, 2008;Fujita et al, 2009;Abdeen et al, 2010;Deyholos, 2010;Mizoguchi et al, 2010). These experiments have substantially increased our knowledge of molecular responses under severe drought stress, but they do not always reflect physiological conditions experienced by drought-stressed soil-grown plants (Bechtold et al, 2010(Bechtold et al, , 2013Harb et al, 2010;Wilkins et al, 2010;Lawlor, 2013;Zhang et al, 2014). Physiological responses such as stomatal conductance, photosynthetic performance, and metabolic changes are usually not measured during the progression of the drought stress, and the varied nature of the stress induction treatments makes comparative analysis between experiments problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, plants achieve a plateau in water status when they are exposed to drought within certain limits of stress severity or within a certain period of time. However, once the threshold is exceeded, plants begin to lose water rapidly [11,43]. In the present study, we inferred that B. humilis had a tolerance for PEG-6000 concentrations between 20% and 30%, thus providing a reference for future work on drought stress in B. humilis.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, we hypothesized that the highest BhCIPK12 expression might occur when plants were treated with approximately 30% PEG. Since gene expression is regulated by a series of physiological and biochemical events, changes in expression levels are not necessarily synchronous with phenotypes or one physiological parameter [43]. Therefore, further studies are needed to confirm the exact PEG treatment concentration and time for the highest expression of BhCIPK12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AM symbiosis increases plant growth and photosynthetic rate which in turn causes increased transport and building up of carbohydrates in cells which act as excellent osmoprotectants to lower osmotic potential (Khalvati et al, 2005). Studies have shown an increase in sugars levels in AM plants exposed to drought in Cyclobalanpsis glauca (Zhang et al, 2014) and in Poncirus trifoliata (Qiangsheng et al, 2006). High sugar content of Poncirus trifoliata confirms a high natural physiological metabolism of AM plants under water stress and well watered conditions leading to accumulation of carbohydrates resulting in decrease of osmotic potential of host cells.…”
Section: Effect Of Am Fungi On Osmotic Adjustmentmentioning
confidence: 99%